On the identity and distribution of the Old World grass feeding leafhopper species Soractellus nigrominutus Evans (Hemiptera: Cicadellidae: Deltocephalinae: Paralimnini) - Webb, M. D.; Yeshwanth, H. M.; El-Sonbati, S. A. (Zootaxa, 2019)
The identity of the Old World grass feeding leafhopper species Soractellus nigrominutus Evans, 1966 is clarified and its distribution revised. Based on examination of material, from throughout its range, the following species are placed as new subjective junior synonyms of S. nigrominutus: S. jianfengensis Xing & Li, 2014, syn. nov., and S. lalianensis Naveed & Zhang, 2018, syn. nov. The following new country records for S. nigrominutus are recorded: Thailand, Nigeria, Kenya, Uganda, Senegal, Ethiopia and Saudi Arabia.